Dynamic failure mechanism of tunnel under rapid unloading in jointed rockmass: A case study. (November 2022) - Yao, Zhigang; Fang, Yong; Yu, Tao; Pu, Song; Luo, Hu; Cui, Jian; Wang, Jun
Highlights: A kind of failure model induced by dynamic unloading in heavily jointed rock. A nonlinear stress-dependent joint model. The unloading process simulation on a tunnel in jointed rockmass. Investigation on the dynamic failure mechanism of tunnel in jointed rockmass. Abstract: Field observations demonstrate that rapid unloading can induce intensive dynamic failure of a tunnel in a jointed rockmass. In this study, we demonstrate the characteristics of the dynamic failure and establish a series of validated discrete element models to investigate the mechanism of the dynamic failure. Our results indicate that the excessive release of strain energy and the complex nonlinear behavior of joints together resulted in the dynamic failure. Primarily, joints can enlarge the unloading disturbance zone (UDZ) and lead to the excessive release of strain energy, especially for a model with smaller joint spacing and higher unloading rate. Secondly, joints can significantly decrease the dependence of the dynamic effect on the unloading rate and expand the unloading time threshold that can induce the dynamic effect, more importantly, the nonlinear variation of joint stiffness not only induces vibration localization but also increases vibration amplitude and reduces vibration frequency.